Crops, Culture, and Colonialism: Agricultural History of Itak Clan, Akwa Ibom State, Nigeria, 1880-1959 (British Journal of Multidisciplinary and Advanced Studies, 2026)
This paper investigates the agricultural history of the Itak clan in Ikono Local Government Area, Akwa Ibom State, with emphasis on the transition from pre-colonial subsistence farming to colonial-era transformations. Using oral traditions, interviews with elders and youths across eleven villages, and limited textual sources, the study reconstructs farming practices, land tenure systems, crop cultivation, and labour organisation.  In the pre-colonial era, agriculture was deeply intertwined with cultural beliefs, communal landholding, and rituals that honoured the soil as “Mother Earth.” Staple crops such as yam and cassava defined social status, while shifting cultivation and age-grade labour groups sustained production. The colonial period introduced mechanised farming and expanded cash crop cultivation; palm oil, coconut, and rubber, reshaped the socio-economic landscape and integrated Itak into global trade networks. Persistent challenges such as land fragmentation, inadequate infrastructure, and misallocation of agricultural inputs revealed the enduring legacies of colonial policies. The study situates Itak’s agrarian history within broader Ibibio and West African contexts highlighted the interplay of crops, culture, and colonialism in shaping rural development.